PERAN ORANG TUA DALAM PERKEMBANGAN ANAK AUTISME DI SKH NEGERI 01 KOTA SERANG - Sukma Damayanti; Yahdinil Firda Nadhirah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Autism is a complex developmental disorder related to communication, social interaction and imaginative activity. Symptoms appear before the age of 3 years. Even if you have infantile autism, the symptoms have been present since you were a baby. This research aims to determine early symptoms and carry out effective early intervention. This can minimize the impact of autism on children and increase children's opportunities to adapt to the disorder and effective developmental interventions and improve the quality of life of children with autism and the parents who care for them. The research method used is descriptive qualitative which describes and explains the role of parents, teachers and the community in improving the quality of education for children with autism at SKH Negeri 01 Serang City. Data collection methods use observation techniques, interviews, documentary research. Data collection tools include audio and video recordings as well as photos of student activities at SKH Negeri 01 Serang City. The data analysis method uses descriptive analysis. Select sources using appropriate sampling methods. The results of research on Autism are very important to know the early symptoms and carry out effective early intervention. This can minimize the impact of autism on children and increase the child's opportunity to adapt to the disorder and effective development interventions and improve the quality of life of children with autism and the parents who care for them. They.